Personal Goals Among Women with Breast Cancer: A Scoping Review and Cohort Study - Chow, Andrea (Université d'Ottawa / University of Ottawa, 2020)
Background: A breast cancer diagnosis may interfere with personal goal-setting, goal pursuit and well-being. Understanding the factors that enable or hinder personal goal-setting and pursuit among women with breast cancer can be a useful element of patient-centred care provision. Objective: To examine the content and pursuit of, and published literature regarding, the personal goals set by women with breast cancer. Methods: Study 1 was a scoping review of the published literature on personal goal-setting by women with breast cancer. Study 2 was a mixed-methods, cohort study with women recently diagnosed with breast cancer to identify their goals, whether they were able to pursue them, and barriers and facilitators of their goals. Results: Study 1: Twelve studies were included. Eight studies included an intervention; completeness of reporting intervention elements varied widely. None of the studies used validated instruments to elicit personal goals. Study 2: Eight participants enrolled and six completed the study. Health, psychological, social, and leisure goals were commonly identified. Women were moderately successful at pursuing their important goals. Perceived enablers and barriers to goal pursuit were identified. Conclusion: Findings on personal goals and personal goal-setting interventions that could help facilitate the development or enhancement of interventions for women with breast cancer to set and pursue their important personal goals.
Keywords: personal goals; breast cancer